Faktor-Faktor yang Mempengaruhi Variasi Tarif Pajak Efektif Perusahaan: Studi Terhadap Perusahaan yang Terdaftar di BEI Tahun 2002 – 2006 - Gatot Soepriyanto (Bina Nusantara University, 2011)
This paper analyzes the determinants of variability in corporate effective tax rates (ETRs) in a multivariate framework, using 2002 – 2006 Indonesian listed companies’ micro-level data. Specifically, I examined the association between effective tax rates (ETRs), firm size and variable proxying for firm’s capital structures and asset mix while controlling from profitability. This study’s present evidence that ETRs are associated with the asset mix (level of capital intensity and inventory intensity) and return on assets. However, results also show that ETRs are not associated with size and firm’s capital structure. Additionally, I controlled industry membership in sensitivity analysis because these firm specific characteristics might differ systematically by industry. To ensure the robustness of the result, diagnostic check was also performed. Related to the 2008 tax law amandement, this research can contribute to tax authority in order to identify firms that still have the potential to pay more taxes by looking at their capital intensity and inventory intensity.